Revisiting the Concept of Peace: A Sociological Perspective - Sidik, Mohamad Dindin Hamam; Setia, Paelani (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2024)
In the ever-changing global context, understanding peace has become a primary focus across various disciplines, including sociology. The sociological paradigm offers a rich and relevant perspective in understanding the dynamics of conflict, reconciliation, and post-conflict development. However, there is still a need for deeper exploration of the concept of peace within the sociological context. This research aims to investigate the evolution of the concept of peace from a sociological perspective, ranging from classical to contemporary thoughts, and to explore the implications of the sociological paradigm in peace practices and policies. This study utilizes a literature review approach to gather and analyze prominent works in sociology relevant to the concept of peace. The analysis is conducted on the views of leading sociological thinkers and relevant research findings. The findings from this literature review indicate that the sociological paradigm provides profound insights into the evolution of the concept of peace, from classical thinkers such as Durkheim, Weber, and Marx, to contemporary approaches such as critical theory and feminism. The practical implications of the sociological paradigm in conflict resolution, reconciliation, and post-conflict development are also explored. This research underscores the importance of the sociological paradigm in understanding and resolving conflicts and post-conflict development. By considering the complexity of social, political, and cultural dynamics and applying a holistic and contextual approach in designing peace strategies, sociology can make a valuable contribution to promoting sustainable and inclusive peace.